MOBILE APPLICATIONS FOR LEARNING ENGLISH AS A MEANS OF ORGANIZING STUDENTS’ INDEPENDENT WORK (ResearchJet Journal of Analysis and Inventions, 2021)
The article is devoted to the actual problem of the possibilities of using information and communication technologies in the process of teaching a foreign language. The author reveals the concept of mobile learning and considers its advantages in teaching foreign languages. The article provides a brief overview of mobile applications for teaching English and the experience of their use in the independent work of students.